2020
DOI: 10.3389/fchem.2020.596658
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on Rare Earth Upconversion Nanomaterials for Combined Tumor Near-Infrared Photoimmunotherapy

Abstract: Cancer has been threatening the safety of human life. In order to treat cancer, many methods have been developed to treat tumor, such as traditional therapies like surgery, chemotherapy, radiotherapy, as well as new strategies like photodynamic therapy, photothermal therapy, sonodynamic therapy, and other emerging therapies. Although there are so many ways to treat tumors, these methods all face the dilemma that they are incapable to cope with metastasis and recurrence of tumors. The emergence of immunotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 165 publications
0
5
0
Order By: Relevance
“…Based on the synergistic effects between chemoradiation and immunity, this study explored the possibility of concurrent chemoradiation therapy combined with REC in the treatment of late-stage NSCLC (39)(40)(41). This study showed that the ORR in the experimental group was better than that in the control group, indicating that the short-term treatment effect of combining REC was better (42)(43)(44). REC can reduce the expression of PD-1 and PD-L1 proteins, block their downstream immune suppressive signaling pathways, thereby preventing their impact on the immune function of the body, and subsequently preventing tumor immune escape.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the synergistic effects between chemoradiation and immunity, this study explored the possibility of concurrent chemoradiation therapy combined with REC in the treatment of late-stage NSCLC (39)(40)(41). This study showed that the ORR in the experimental group was better than that in the control group, indicating that the short-term treatment effect of combining REC was better (42)(43)(44). REC can reduce the expression of PD-1 and PD-L1 proteins, block their downstream immune suppressive signaling pathways, thereby preventing their impact on the immune function of the body, and subsequently preventing tumor immune escape.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their high light conversion efficiency, various inorganic materials have been explored as novel phototherapeutic agents, including carbon dots, [72] black phosphorus nanosheets, [73] and rare earth element upconversion nanoparticles. [74] In a recent study, a CoWO 4-x nanoplatform was constructed with a wide absorption spectrum, and it was capable of generating of both heat and ROS upon irradiation for dual PTT and PDT. [75] When using inorganic materials, their possible accumulation in tissues and associated toxicity risks must be considered [76] ; those with good biodegradability and biocompatibility are desirable.…”
Section: Enhanced Absorption and Ros Generation Efficiencymentioning
confidence: 99%
“…Ultrasmall-sized (such as < 5 nm) UCNPs have poor UCL efficiency. However, large UCNPs cannot be eliminated by the kidney, and the elimination is mainly through the biliary tract, but this route needs more time and has a potential risk of hepatotoxicity ( Chen et al, 2020 ).…”
Section: Limitations For Upconversion Nanoparticle-based Antibacteria...mentioning
confidence: 99%